Defining assessment literacy: Is it different for language testers and non-language testers?. (July 2013) - Jeong, Heejeong
Language assessment courses (LACs) are taught by professionals who have majored in the area of language testing (language testers or LTs), but also by others who come from different language-related majors (non-language testers, non-LTs). Different language assessment courses may be developed, depending on who teaches the course and the instructors' understanding of assessment literacy. This study seeks to investigate the effect instructors bring in shaping the characteristics (i.e., content and structure) of language assessment courses. Findings from an online instructor survey ( N = 140) and in-depth follow-up phone interviews ( N = 13) show that there are significant differences in the content of the courses depending on the instructors' background in six topic areas: test specifications, test theory, basic statistics, classroom assessment, rubric development, and test accommodation. Interview results confirm non-LTs are less confident in teaching technical assessment skills compared to LTs and have a tendency to focus more on classroom assessment issues. The paper ends by stressing the importance of possessing a common understanding of assessment literacy among stakeholders within the testing community, but also among non-LTs who teach language assessment courses so as to maintain course quality and to better meet student teachers' needs.